DAMPAK PENYAKIT MULUT DAN KUKU TERHADAP USAHA PETERNAKAN SAPI PERAH DI WILAYAH KERJA KOPERASI PRODUKSI SUSU (KPS) BOGOR - Anggia Putri, Meliani; Hermawan; Firman, Achmad (Jurnal Peternakan Nusantara, 2024)
Research on "The Impact of Foot and Mouth Disease on Dairy Farming Businesses in Koperasi Produksi Susu (KPS) Bogor Working Area" has been carried out in the KPS Bogor Dairy Cattle Farming Business Area (KUNAK), Cibungbulang District, Bogor Regency in January 2024. The aim of the research is to determine changes in population, milk production and quality of dairy cows, as well as farmer acceptance due to the impact of FMD in KUNAK as the Bogor KPS working area. The method used is a survey method using a qualitative descriptive and quantitative approach with a sample of 46 breeders used in the research. The results of this research indicate that there were significant changes in population numbers, milk production, and farmer acceptance before and during the existence of PMK at KUNAK KPS Bogor. The results of this study also showed that there were no significant changes in the quality of fat and protein levels before and during FMD.